(untitled) (Journal of Human Sciences, 2026)
This research examines the criminal protection of honor and chastity under the Libyan Penal Code through a critical and analytical study of Articles (375), (420 bis), and (424). The study is based on the premise that, although the protection of honor represents a legitimate social value, the current legislative framework reflects a traditional approach that no longer aligns with contemporary principles of criminal justice, equality before the law, and the protection of human dignity. The research demonstrates that Article (375), which grants a mitigating excuse for killing committed under the pretext of defending honor, undermines the fundamental right to life and institutionalizes gender-based discrimination by granting unjustified privileges to male offenders. Article (420 bis), despite its importance in combating sexual harassment, suffers from vague wording, limited scope, and inadequate penalties, and fails to address modern forms of harassment, particularly those occurring in digital environments. Article (424), which allows the suspension of criminal proceedings or the execution of punishment upon marriage between the offender and the victim, represents one of the most controversial provisions, as it opens the door to impunity under the guise of social concealment and fails to ensure the free and genuine consent of the victim. The study concludes that these provisions suffer from structural and procedural deficiencies that weaken criminal protection, legitimize discrimination, and create avenues for evading punishment. Accordingly, the research calls for a comprehensive legislative reform that aligns Libyan criminal policy with modern legal standards, prioritizes individual dignity and equality, and ensures effective protection of victims without compromising the principles of criminal justice.